Paraffin wax embedded muscle is suitable for the diagnosis of muscular dystrophy. Issue 7 (1st July 2001) - Sheriffs, I N; Rampling, D; Smith, V V
Abstract : Aim —At present, the diagnosis of muscular dystrophy is made by means of immunohistochemistry on frozen sections. The aim of this study was to develop a sensitive and reproducible immunohistochemical method for use on formalin fixed, paraffin wax embedded sections for the demonstration of dystrophin associated proteins and other muscle associated antigens. Methods —All the cases studied were from the files of the department of histopathology, Great Ormond Street Hospital for Children NHS Trust. Immunohistochemistry was performed on paraffin wax embedded sections with heat mediated antigen retrieval and overnight incubation with the antibodies at room temperature. Four different pretreatment buffers were tested in the attempt to optimise the immunostaining. Frozen sections were run in parallel for direct comparison. Results —All the antibodies except δ sarcoglycan gave strong, consistent immunostaining in paraffin wax embedded sections, comparable with the frozen sections. The most consistent results were obtained using citrate/EDTA as the pretreatment buffer. Conclusion —A reliable and reproducible technique has been established, using a heat mediated citrate/EDTA buffer antigen retrieval method, which works well for most of the antibodies needed to make the diagnosis of muscular dystrophy in formalin fixed, paraffin wax embedded sections. This technique overcomes some of the inherent problems encountered using frozen muscle tissue and it could become a valuable tool for the diagnosis of muscular dystrophy.